Effect of specimen history on structure and in-plane permeability of woven fabrics - Endruweit, Andreas; Zeng, Xuesen; Long, Andrew C. (SAGE, 2015)
Before being processed into composites, reinforcement fabrics may undergo repeated involuntary deformation, the complete sequence of which is here referred to as specimen history. To mimic its effect, fabric specimens were subjected to sequences of defined shear operations. For single fabric layers with unconstrained thickness, quantitative evaluation of photographic image data indicated that repeated shear deformation results in a residual increase in inter-yarn gap width. This translates into an increase in measured fabric permeabilities in multi-layer lay-ups at given compaction levels. The extent of both interrelated effects increases with increasing yarn density in the fabric and with increasing maximum angle in the shear history. Additional numerical permeability predictions indicated that the increase in permeability may be partially reversed by through-thickness fabric compression. The observations suggest that the effect of involuntary deformation of the fabric structure can result in variations in the principal permeability values by factors of up to 2.